PENGARUH KUALITAS PELAYANAN DAN CRM ( CUSTOMER RELATIONSHIP MANAGEMENT ) TERHADAP KEPUASAN PELANGGAN PADA PT. EKAPUTRA PRADA INDONESIA - Tesya Novia; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at PT. Ekaputra Prada Indonesia, located on Garuda Sakti Street, Simpang Baru, Tampan, Pekanbaru, Riau. The purpose of this study was to determine the effect of service quality and crm on customer satisfaction  at PT. Ekaputra Prada Indonesia partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study are all consumers who purchase the product at PT. Ekaputra Prada Indonesia in the last year of 2020 totaling 59 consumers. Where the samples in this study are consumers of PT. Ekaputra Prada Indonesia as many as 59 respondents. To determine the sample using the Census Method. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale.From the analysis of data which includes validity, reliability, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and f test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, service quality on customer satisfaction is t arithmetic (7.972)> t table (1,67203) means that service quality has a significant effect on customer satisfaction. Second, the crm on customer satisfaction is t arithmetic (8.069)> t table (1.67203) means that the crm significantly influences customer satisfaction. The f test results of service quality and crm have a significant effect on customer satisfaction, namely f arithmetic (45.157)> Ftable (3.16). This means that service quality and crm simultaneously have a significant effect on customer satisfaction at PT. Ekaputra Prada Indonesia. Keywords: Service Quality, CRM, Customer Satisfaction